USING THINK PAIR SHARE COMBINED WITH PICTURES TO DEVELOP THE SPEAKING SKILLS OF THE VOCATIONAL HIGH SCHOOL STUDENTS - Mariana Suryanti; Ida Bagus Nyoman Mantra; Anak Agung Istri Yudhi Pramawati (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2022)
Having good speaking skills is highly important for us to communicate in English. This is due to the fact that speaking is the first impression in communicating with others. Therefore, this study intends to improve students' speaking skills through think pair share combined with pictures. Preliminary research showed that vocational high school students encountered problems in speaking, particularly fluency, comprehension, and grammar. Moreover, the research objective was to know whether the speaking skill of vocational high school students could be improved through think pair share combined with pictures. This study made use of a classroom action research design. The research instruments administered to collect the data were in the form of a test and a post-test. The data were analyzed by comparing the pre-test and post-test results. As the supporting data, the questionnaire was also administered at the end of the last cycle. The results showed positive responses on the implementation of think pair share combine with picture. Based on the research findings, the speaking skills of vocational high school students could be improved using think pair share combined with pictures.